(untitled) (Pulse, 2022)
Intravascular embolization of bullets and other foreign bodies is a rare complication of penetrating trauma. It can represent a diagnostic challenge because it may present in various and unexpected ways. We report the case of a 65-year-old male who sustained shotgun pellet emboli to left ulnar artery following a right and left upper extremity gunshot injury. Pulse volumel.11 January-December 2018-2019 p.33-37